Seliverstova Yu.A. Administration process and administrative proceedings: problems and future - V. V. Golovko; Yu. A. Seliverstova (Правоприменение)
The subject is administrative proceedings in the system of judicial proceedings used in Russia.The purpose of the article is definition of the essence of both legal proceedings in general and administrative proceedings in particular, as well as its varieties.Methodology includes methods of complex analysis and synthesis of the Russian legislation and scientific sources, as well as formal-logical logical interpretation of legal rules and scientific papers.Main results. It seems reasonable to be guided by the position of the legislator, according to which each constitutionally defined type of legal proceedings corresponds to a specific procedural form, each of which is fixed exclusively in the corresponding independent federal law. The separation of civil and commercial proceedings is of a functional nature, taking into account the totality of the specifics and the subject composition of the civil cases under consideration. Currently, in the Russian Federation, administrative proceedings are carried out in at least two independent procedural forms. Administrative court proceedings are judicial administrative proceedings, the human rights essence of which is the procedural activity of the court for the actual consideration and resolution of administrative cases and cases of administrative violations. The concept of administrative proceedings is part of a broader concept of administration process, which, in addition to considering a case accepted for trial on the merits, includes the procedural activity of the court at the stage before the acceptance of administrative claims submitted to the court under the Code of Administrative Procedure of the Russian Federation. The administration process is exclusively judicial in nature and does not preclude the activities of quasijudicial bodies to consider disputes with citizens and organizations on issues of disagreement of the latter with the actions (inaction) of executive authorities and their officials and their decisions.Conclusions. The components of the concept of administrative proceedings are proceedings in administrative and other cases arising from public relations (public law disputes) and judicial proceedings in cases of administrative offenses. Public law disputes and proceedings in cases of administrative offenses include a public authority as one mandatory party, nevertheless, public law disputes are of a claim nature, whereas proceedings on an administrative offense have a tort content.